A Practical Training Program for Peripheral Radial Artery Catheterization in Adult Patients: A Prospective, Randomized Controlled Trial. (October 2016) - Nakayama, Yoshinobu; Inagaki, Yuko; Nakajima, Yasufumi; Sessler, Daniel I.; Mukai, Nobuhiro; Ogawa, Satoru; Mizobe, Toshiki; Sawa, Teiji
Abstract : Background: The main cause of unsuccessful peripheral radial artery catheterization using traditional palpation is imprecisely locating the arterial center. The authors evaluated factors causing disparities between the arterial centers determined by palpation versus ultrasound. The authors applied them to create and test a novel catheterization training program. Methods: The arterial central axis was determined by ultrasound and palpation in 350 adults. Potential independent predictors of disparity included sex, body mass index, pulse pressure, transverse arterial diameter, subcutaneous arterial depth, chronic hypertension, and experience as an anesthesiologist (less than 3 vs. greater than or equal to 3 yr). Using the results, the authors developed a radial artery catheterization training program. It was tested by enrolling 20 first-year interns, randomized to a training or control group. The time to successful insertion was the primary outcome measure. The success rate and time required for catheterization by palpation were evaluated in 100 adult patients per group. Results: Independent predictors of central axis disparity were pulse pressure, subcutaneous radial artery depth, years of experience, and chronic hypertension. Training improved the catheterization time (training group 56 ± 2 s vs. control group 109 ± 2 s; difference –53 ± 3 s; 95% CI, –70 to –36 s; P < 0.0001) and total success rate (training group 83 of 100 attempts, 83%; 95% CI, 75 to 90 vs. control group 57 of 100, 57%; 95% CI, 47 to 66; odds ratio, 3.7; 95% CI, 2.7 to 5.1). Conclusions: Misjudging the central axis position of the radial artery is common with a weak pulse and/or deep artery. The authors' program, which focused on both these issues, shortened the time for palpation-guided catheterization and improved success. Abstract : Using data from radial artery ultrasound in 350 adults, a training program for palpation-guided catheterization was devised; completion of this program resulted in shorter insertion time (56 ± 2 vs. 109 ± 2 s) and greater success (83 of 100 vs. 57 of 100 attempts) versus controls.